Development of real-time ultrasonic sensoring system to measure distance using labview - Norsukmawati, Ishak (2012)
This project involves the implementing of ultrasonic sensor for industrial related applications in real-time. Ultrasonic sensor works on the area from 40 KHz to 400 KHz. To detect the distance of the object, ultrasonic sensor measures the time from the transmission of sonic wave to reception of the sonic wave. In process industry, it present the ideal solution to level detection of non-contact level sensing of highly viscous liquids in process industry. It also used to measurement of flow, crack detection and tank level measurement. The sensor system should have DAQ capabilities using NI DAQ card USB-6009. By using the DAQ card, the data will be transfer from sensor to computer. Input and output data will be transfer through digital signals or analog signals or channels. DAQ card operate by utilizing both DAQ hardware and software. By using the LabVIEW programming language, the interface for the sensor system will be developed and LabVIEW also used to communicate with DAQ hardware. In LabVIEW, we build a block diagram contains to control the front panel objects. The developed sensor should capable of measurement in real-time. The system also capable for data storage and data retrieval for further analysis.